'of mens and them': Caribbean English in V.S. Naipaul's "Love, Love, Love Alone" - Barros, Rita Queiroz de (2013)
Though literature is dominated by standard language, it often makes use of other linguistic varieties. This polyglossic device has been a resource of Anglophone literature since the 14th century, with mimetic, comic and/or ideological functions, and earned the attention of literary critics and, more recently, of translation studies researchers. However, though linguistic realism is not a goal of literary texts, it seems reasonable to claim that the analysis of the linguistic variation in literature will benefit from the teachings of linguistics. Such conviction is tested in this paper by means of an analysis of V. S. Naipaul’s semi-autobiographical “Love, Love, Love, Alone”, set in Trinidad, in which Standard English is used by non-local characters and the narratorial voice and Caribbean English is brought into dialogue by Trinidadian characters, including the participant narrator. The scrutiny of the text and the consideration of both technical descriptions of the linguistic situation of Trinidad and the concepts of linguistic repertoire, code switching and hypercorrection have unveiled a consistency in the recreation of local English that critics consider untypical of literature and shown that the English language Naipaul claimed as his was probably less monolithic than implied so far.